Posyandu Elderly As An Alternative Health Care Program - Harahap, Arman (CV. Inara, 2021)
The elderly population continues to increase from year to year, so it takes the optimization of vehicle services for the elderly as the elderly posyandu (poslan). The purpose of this community is to overcome the problems of health care programs in the Village of T. Flush considered not optimal. In addition to the program services poslan that is not optimal, the limitations of the health facilities that support the program are also still to be dep. Method of problem solving is done by forming a cadre of poslan,socialization poslan, training on the task 5 of the table (physical examination and independence of the elderly, charging KMS and laboratory skills simple), the practice of implementation of poslan, the provision of facilities medical devices and simple laboratory and carry out activities supporting the health of the elderly such as gymnastics elderly. The results of the activities of Science and technology For Society (IbM) which was conducted on both the partners is the availability of the health care system 5 the table on the second poslan and the availability of a cadre of elderly well-trained and the availability of means of medical equipment to conduct the examination of physical health and mental-emotional, the availability of a simple laboratory as a facility used for the early detection of the disease in the elderly. Conclusion of IbM activities can increase the range of health services for the elderly and is formed of the health service in accordance with the needs of the elderly so that can improve the health of the elderly.